Comparison of patients with and without pre-existing lymphoma at diagnosis of primary Sjögren's syndrome. (4th May 2019) - Vasaitis, L; Nordmark, G; Theander, E; Backlin, C; Smedby, KE; Askling, J; Rönnblom, L; Sundström, C; Baecklund, E
Abstract : Objective : In the 2016 American College of Rheumatology/European League Against Rheumatism classification criteria for primary Sjögren's syndrome (pSS), pre-existing lymphoma is not an exclusion criterion for pSS diagnosis, as in earlier criteria. We aimed to explore whether there are differences between pSS patients with and without pre-existing lymphoma at pSS diagnosis. Method : Patients with ICD-7–10 codes for Sjögren's syndrome (SS) and a diagnosis of malignant lymphoma before or after SS diagnosis were identified by linking the Swedish Patient Register 1964–2007 with the Cancer Register 1990–2007 (n = 224). Clinical data were collected from medical records. Lymphoma diagnoses were evaluated by tissue review. Characteristics of pSS patients with and without pre-existing lymphoma were compared. Results : We identified 107 patients with pSS as the reason for an SS diagnosis code and a verified lymphoma. Of these, 18 (17%) had a pre-existing lymphoma at pSS diagnosis, defined as lymphoma diagnosed before or within 6 months of pSS diagnosis. Male gender (39% vs 10%, p = 0.006), enlarged lymph nodes during the pSS disease (61% vs 27%, p = 0.01), mucosa-associated lymphoid tissue (MALT) lymphoma (50% vs 22%, p = 0.02), and salivary gland lymphoma (61% vs 26%, p = 0.006) were more common in patients with a pre-existing lymphoma at pSS diagnosis. Other pSS characteristics were similar. Conclusion : In a substantial proportion of patients, particularly in men, pSS remains undiagnosed until after lymphoma diagnosis. The study highlights the importance of pSS investigation in patients with lymphoma, especially MALT lymphoma, in the salivary glands.